2012
DOI: 10.1063/1.3676074
|View full text |Cite
|
Sign up to set email alerts
|

Production of bio-oil from mahua de-oiled cake by thermal pyrolysis

Abstract: Articles you may be interested inEffect of Co-pyrolysis of mahua seed and waste polystyrene on quality of liquid fuel J. Renewable Sustainable Energy 6, 053142 (2014); 10.1063/1.4900550 Pyrolysis kinetics of de-oiled cakes by thermogravimetric analysisDe-oiled cakes, a source of biomass in the form of agriculture residue, could be an ideal source for the production of bio-fuels that can be substituted with conventional fossil fuels. In this study, pyrolysis of mahua de-oiled cake (Madhuca indica) was carried i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Depending on the operating requirements, pyrolysis process is often split into three types: instant pyrolysis, rapid pyrolysis, and traditional pyrolysis. Several kinds of research have been conducted on the pyrolysis process for the production of biodiesel from edible and nonedible vegetable oils [73].…”
Section: Pyrolysismentioning
confidence: 99%
“…Depending on the operating requirements, pyrolysis process is often split into three types: instant pyrolysis, rapid pyrolysis, and traditional pyrolysis. Several kinds of research have been conducted on the pyrolysis process for the production of biodiesel from edible and nonedible vegetable oils [73].…”
Section: Pyrolysismentioning
confidence: 99%
“…One exception is with use as fish feed; Alexander et al did not identify any toxicity in fishes . In recent years, Mahua seedcake has been used as a feedstock for pyrolysis and anaerobic digestion. , Gupta et al reported that detoxified Mahua seedcake showed significantly better results compared to the raw cake in biogas production, although utilization of raw cake for biogas was still a reasonably effective application.…”
Section: Potential Sources Of Low-cost Plant Feedstockmentioning
confidence: 99%
“…Pyrolysis is one of the most practical thermochemical processes for transforming biomass into valuable synthetic fuels, which can be used as a source of energy. Literature reports the thermal degradation studies of different categories of biomass feedstock such as bark, 1,2 wood, 3,4 agricultural wastes/residues, 5,6 nuts and seeds, 7,8 algae, 9,10 grasses, 11 forestry residues, 12,13 cellulose and lignin, 14 and miscellaneous for bio oil production 15 . The important outcome of the above reported works are summarized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Volli et al conducted pyrolysis experiment of Mahua (Madhuca Indica) deoiled‐cake in a semi‐batch reactor at different temperatures ranging from 350–600°C with an increment of 50°C and heating rate of 25°C/min. and reported the effect of pyrolytic temperature on product distribution 6 . Low temperature conversion pyrolysis of castor seeds (Ricinus communis) at 380°C under a constant nitrogen flow 7 .…”
Section: Introductionmentioning
confidence: 99%